The Case for an Implied Warranty of Quality in Sales of Commercial Real Estate - Frona M. Powell; Jane P. Mallor (Washington University Law Quarterly, 1990)
Although the application of an implied warranty of quality is now widespread in the sale of new homes, relatively few courts have considered whether implied warranty protection should extend to purchasers of commercial property. Of these courts, some have rejected the application of the warranty based on the assumption that a purchaser of commercial property is capable of acting for his own protection. Other courts, minimizing the significance of the purchaser's investor status, have held that an implied warranty of quality applies in sales of commercial as well as residential property. This Article will demonstrate that an implied warranty of quality should be imposed in sales of commercial property and will make recommendations about the application of such a warranty. Part I examines the evolution, policies, and scope of the implied warranty of habitability as that warranty has applied to sales of residential property. Part II examines the divergent approaches that courts have used in cases concerning sales of commercial property. Part III then evaluates whether the rationales supporting the implied warranty of habitability apply in sales of commercial property, and contends that they do. Finally, the Article proposes standards for the application of an implied warranty of quality tailored to the issues likely to confront courts with respect to sales of commercial property.
Keywords: Vendors (Real property); Warranty